Low-level neurostimulation of the renal nerves as a potential therapeutic strategy for hypertension treatment - Salman, Ibrahim M.; Ameer, Omar Z.; Hassan, Sarah F.; Sridhar, Arun; Hsieh, Yee-Hsee; Lewis, Stephen J. (Frontiers in Pharmacology, 2025)
BackgroundNeurostimulation is an emerging treatment for conditions like hypertension. The renal nerves, comprising sensory afferent and sympathetic efferent fibers, are crucial for blood pressure (BP) regulation. The inhibitory reno-renal reflex, where central integration of renal sensory input reduces sympathetic outflow and systemic BP, presents a promising target for neurostimulation interventions. We therefore investigated renal nerve stimulation (RNS) as a potential hypertension therapy.MethodsAnesthetized male spontaneously hypertensive rats (SHRs) were subjected to low-level RNS at 0.5 mA pulse amplitude and 0.5 ms pulse width for 30 s delivered to the left intact renal nerve at 2.5 and 5.0 Hz. Mean arterial pressure (MAP), heart rate (HR), hindquarter blood flow (HQF), and ipsilateral renal cortical blood flow (RCF) were recorded. Hindquarter resistance (HQR) and renal cortical resistance (RCR) were derived from MAP and flow values.ResultsRNS significantly reduced MAP, with similar depressor responses at 2.5 (27 ± 3 mmHg) and 5.0 Hz (37 ± 8 mmHg). RNS substantially increased HQF and reduced HQR, with comparable effects at both frequencies. A 5-Hz stimulus markedly reduced RCF and increased RCR of the ipsilateral kidney. When the stimulation frequency was lowered to 2.5 Hz, the changes in RCF and RCR were nearly indistinguishable from baseline.ConclusionLow-level RNS effectively lowers BP in the SHR model of hypertension and may offer a promising therapeutic alternative for hypertension treatment. Physiologically, the observed clinically relevant reductions in BP were primarily due to reductions in vascular resistance. Adjusting stimulus levels can achieve desired hypotensive responses without compromising ipsilateral renal blood supply, typically affected by direct renal sympathetic fiber stimulation.